Biomitografia zakwestionowana. Sendlerowa. W ukryciu Anny Bikont jako performans tekstualny - Żarnecka, Paulina (Przestrzenie Teorii, 2020)
The article is a performative interpretation of Sendlerowa. W ukryciu, a biography of Irena Sendlerowa by Anna Bikont. The author of the article presents the biography as a textual performance, whose aim is to contest the well-known image of Irena Sendlerowa (described within the category of biomythography introduced by Michael Benton). The author analyses how Anna Bikont distances herself from the biomythography and reintroduces the parts of Sendlerowa’s biography that had been omitted for years through being incompatible with the role of a national hero. She also evaluates the extent to which biography can serve as a critical tool with respect to Polish historical policy.